The impact of the body micro-environment on female infertility - Rosita Verteramo; Matteo Pierdomenico; Giulia Gerolin; Pantaleo Greco; Carmelia Milano (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2023)
Infertility influences 15% of reproductive-aged couples in the world and the same percentage has been counted in Italy. Male and female causes of infertility are identified in 20% - 30% and 20% - 35% of couples, respectively; in 10% - 20% of cases, no cause is found. Until the last decade, a lot of studies have analyzed both modifiable factors (tobacco, alcohol, diet factors, overweight, infections) and non-modifiable factors (parental age, low ovarian reserve, etc.). Probably there is a connection between modifiable and non-modifiable causes of infertility, that together increase the failure of reproduction. This review aims to analyze the influence of the microenvironment in the female genital tract, particularly to highlight the current literature, published in Italy, on reproductive tract microbiome in different anatomical locations, vagina, endometrium, Fallopian tubes, the intestinal microbiome, and the possible interaction between such microbial communities and infertility. Finally, based on the data presented in this review, we try to encourage future perspectives and research directions in Italy.